Response surface methodology (RSM) mediated interaction of media concentration and process parameters for the pigment production by Monascus purpureus MTCC 369 under solid state fermentation. Issue 1 (3rd January 2017) - Sehrawat, Rachna; Panesar, Paramjit S.; Swer, Tanya L.; Kumar, Anit
Abstract : Purpose: This paper aims to extract colour from micro-organisms (as a source of natural pigments) using agro-industrial substrates to replace synthetic media by solid state fermentation. Nature is filled with colours. Due to health and environmental consciousness among people, use of synthetic colour has declined, and so the need to develop colour from cheap and easily available natural sources (plants, animals, micro-organisms and algae) using a cost-effective technique with higher yield and rapid growth. Monascus purpureus colour is a potent source of compounds (Dimerumic acid, Monacolin-k and -aminobutyric acid) having antimutagenic, antimicrobial and antiobesity, which helps in combating diseases. Design/methodology/approach: Response surface methodology was used to optimise the biopigments extraction from Monascus purpureus using solid state fermentation. Findings: The best optimised conditions for biopigments production using Monascus purpureus MTCC 369 were pH 5.4 at 32°C for 8 days 9 hours (8.9 days) from sweet potato peel and pea pod powder, 7.8 (w/w) and 3.9 per cent (w/w), respectively, which gave a final yield of 21 CVU/g. The model F -value of 69.18 and high value of adjusted determination coefficient 96.00 per cent implies high level of significance of the fitted model. Practical implications: Extracted colour can be used in beverages, confectionery and pharmaceutical industries. Social implications: Colour produced using Monascus purpureus MTCC 369 is a natural source. As consumers are reluctant to use synthetic colour because of the undesirable allergic reactions caused by them, so a biopigment produced is natural colouring compound with wide application in food sector. Originality/value: Selected sources of carbon and nitrogen were not used earlier by any researcher to extract biopigment from Monascus purpureus MTCC 369.